Fundamental laboratory approaches for biochemistry and biotechnology - Ninfa, Alexander J. (John Wiley & Sons, 1998)
An excellent biochemistry laboratory text for advanced undergraduate and first year graduate students in biochemistry and other life sciences, this text provides a logical framework for training students how to approach research problems and conduct and evaluate scientific research. Each chapter provides extensive background on the principles underlying methods used to research, followed by experiments designed to illustrate those